AUDIT OF MUNICIPALITIES AND LOCAL GOVERNMENT UNITS - THE CASE STUDY OF THE CZECH REPUBLIC - Richard POSPISIL (Challenges of the Knowledge Society)
Public economics examines the influence of the state on economic equality and efficiency, and on conduction of business entities in connection with the various tax systems and individual behavior in private consumption. To manage the public economy is thorough knowledge of the real decision-making and allocation mechanisms. From a budgetary perspective, the public economy in the Czech Republic is characterized mainly by the state budget, 6,249 municipal budgets and 14 budgets of local government units. These all units are together subject to annual statutory audit, which mainly represents the analysis of the system of the Audit informative and monitoring indicators (ASIMI). The paper analyzes the outcome of the audit with the use of absolute and relative indicators and suggests possible changes and consolidation of municipal and local government budgets in the Czech Republic.